Self-care practices and associated factors among hypertension patients in public hospitals in Harari regional state and Dire Dawa City administration, Eastern Ethiopia: A multi-center cross-sectional study - Abdisa, Lemesa; Balis, Bikila; Shiferaw, Kasiye; Debella, Adera; Bekele, Habtamu; Girma, Sagni; Mechal, Ayalnesh; Amare, Eldana; Kechine, Temesgen; Tari, Kajela; Nigussie, Kabtamu; Assefa, Nega; et al. (Frontiers in Public Health, 2022)
Abstract Introduction: Hypertension is a silent killer that causes serious health issues in all parts of the world. Hypertension is a risk factor for cardiovascular disease, stroke, and kidney disease. Self-care practices have been identified as an important component of hypertension management. Despite the government's commitment and the interventions of various stakeholders, the burden of hypertension and its sequel remain unabated. Though few documented studies pointed out that self-care practices related to hypertension play a vital role in controlling and managing high blood pressure, still there is poor self-practice Methods: Hospital-based cross-sectional study was employed from June 15 to July 15/2021 among 415 hypertensive patients at the public hospitals in the Harari region and Dire Dawa City Administration. The data were collected by using systematic sampling were coded, double entered to Epi data version 3.1, and exported to SPSS version 24 for analysis. Descriptive statistics were used to present frequency distributions. Variables with a P-value <0.25 during bivariate analysis were entered into the multivariate logistic regression models to control for all possible confounders. Odds ratio along with 95% CI were estimated to measure the strength of the association and the level of statistical significance was declared at a p-value of less than 0.05. Results: Two hundred twenty 52% (95% CI, 48.2–58%) of the patients had good hypertension self-care practices. Attending formal education (AOR = 3.45, 95% CI: 2.1-4.85), having good knowledge about hypertension (AOR= 1.5, 95% CI: 1.17-2.1) 1.5, abstain from chewing khat (AOR= 2.01, 95% CI: 1.44-3.94), having strong social support (AOR= 1.9, 95% CI: 1.16-3.1), and absence of depression (AOR= 2.03, 95% CI: 1.43-3.92) were significantly associated with good self-care practices at p-value < 0.05. Conclusion: This study pointed out that about half of the participants have good self-care practices. Formal education, good knowledge about hypertension, abstaining from khat chewing, good social support, and no depression was positively associated with self-care practices. The policymakers should consider these factors in specific public health interventions on hypertension self-care practices, as well as in strengthening the current non-communicable diseases control programs. Keywords: Self-care, hypertensive, associated factors, Eastern Ethiopia.